Excellence in achievement contexts: psychological science applications and future directions - Araújo, Liliana S. (2007)
The study of human excellence has always been present in the development of psychological science, although its theory, research, and practice focus have been mainly on negative and pathological issues. Many authors have attempted to explain and understand youth and adults’ exceptional achievements in several achievement domains, such as science, art, or sports. Here, we consider three main different approaches that study excellence. There are those which focus on natural talent, those which propose intensive training and practice as main factors of high and outstanding performances, and those which define excellence in the context of wisdom. Analyzing the current literature, we can distinguish training, deliberate practice, and exceptional performance specificity resulting from a precocious involvement and commitment to a specific domain as main points of convergence. Cognitive, motivational, affective, and personality characteristics, as well as contextual elements such as learning experiences and supportive environments, are emphasized as crucial factors in the developmental process of excellence. This concern and interest in human excellence appears to be shared by professionals from different domains. New challenges for future research in this field are presented.